2022
DOI: 10.3389/fimmu.2022.893792
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Lipid Mediators of Inflammation in Lungs of SARS-CoV-2 Infected Mice

Abstract: Coronavirus disease 19 (COVID-19) is the clinical manifestation of severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection. A hallmark of COVID-19 is a lung inflammation characterized by an abundant leukocyte infiltrate, elevated levels of cytokines/chemokines, lipid mediators of inflammation (LMI) and microthrombotic events. Animal models are useful for understanding the pathophysiological events leading to COVID-19. One such animal model is the K18-ACE2 transgenic mice. Despite their importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Although the pathogenicity of SARS-CoV-2 is complex, stimulation of pathogen-associated pattern recognition receptors including toll-like receptors 26,27 and retinoic acid-inducible gene-I receptors 28 by viral components is the principal driver of lung inflammation, and subsequent alveolar tissue damage. In the present study, the bioinformatic analysis of lung tissue transcriptomes demonstrated that the COVID-19 mimicking animal model with SARS-CoV-2 spike protein and poly (I:C) recapitulated key biological responses in inflammatory and cell death pathways induced by SARS-CoV-2 [32][33][34][35][36][37] . Moreover, alveolar cell death patterns in our COVID-19 animal model were similar to those 16 observed in human COVID-19 29,30 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although the pathogenicity of SARS-CoV-2 is complex, stimulation of pathogen-associated pattern recognition receptors including toll-like receptors 26,27 and retinoic acid-inducible gene-I receptors 28 by viral components is the principal driver of lung inflammation, and subsequent alveolar tissue damage. In the present study, the bioinformatic analysis of lung tissue transcriptomes demonstrated that the COVID-19 mimicking animal model with SARS-CoV-2 spike protein and poly (I:C) recapitulated key biological responses in inflammatory and cell death pathways induced by SARS-CoV-2 [32][33][34][35][36][37] . Moreover, alveolar cell death patterns in our COVID-19 animal model were similar to those 16 observed in human COVID-19 29,30 .…”
Section: Discussionmentioning
confidence: 58%
“…4A). We found 6 publicly available lung tissue RNA-seq datasets of mice infected with SARS-CoV-2 from the NCBI Gene Expression Omnibus database (Table S3) [32][33][34][35][36][37] and performed comparative analysis for all the datasets including the data obtained from this study. Comparison of differentially expressed genes (DEGs) showed only small overlaps, even when comparisons were performed among the infection models (Table S4).…”
Section: Intratracheal Instillation Of Sars-cov-2 Spike Proteins Comb...mentioning
confidence: 99%
“…Three days postinfection, cytokine load and antiviral related genes were measured in mouse lungs. No change in body weight or temperature was observed at this time (30). As shown in Fig.…”
Section: Viral Loads and Host Gene Modulation Following Infection By ...mentioning
confidence: 59%
“…Three days post-infection, the mice were euthanized and their lungs used for further analyses. No change in body weight or temperature was observed during this time [ 36 ]. As shown in Figure 1 A,B, all the infected mice had significant pulmonary infectious viral loads and expressed abundant SARS-CoV-2 E gene copy numbers.…”
Section: Resultsmentioning
confidence: 99%